2014
DOI: 10.1371/journal.pone.0090738
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Arbuscular Mycorrhizae on Biomass Production and Nitrogen Fixation of Berseem Clover Plants Subjected to Water Stress

Abstract: Several studies, performed mainly in pots, have shown that arbuscular mycorrhizal symbiosis can mitigate the negative effects of water stress on plant growth. No information is available about the effects of arbuscular mycorrhizal symbiosis on berseem clover growth and nitrogen (N) fixation under conditions of water shortage. A field experiment was conducted in a hilly area of inner Sicily, Italy, to determine whether symbiosis with AM fungi can mitigate the detrimental effects of drought stress (which in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 37 publications
2
33
0
Order By: Relevance
“…Indeed, the activation in the arbuscular mycorrhizal symbiosis of molecular mechanisms common to those of plant pathogens already has been found (Pozo et al 2010). In addition, as suggested above, AMF can reduce the N content of the plant (Saia et al 2014a) or readdress amino acid metabolism to the biosynthesis of secondary compounds (Battini et al 2016;Srivastava et al 2016). Other authors (Briskin et al 2000;Briskin and Gawienowski 2001) also showed that a reduction in N availability increased hypericin content without resulting in nitrogen deficiency symptoms.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Indeed, the activation in the arbuscular mycorrhizal symbiosis of molecular mechanisms common to those of plant pathogens already has been found (Pozo et al 2010). In addition, as suggested above, AMF can reduce the N content of the plant (Saia et al 2014a) or readdress amino acid metabolism to the biosynthesis of secondary compounds (Battini et al 2016;Srivastava et al 2016). Other authors (Briskin et al 2000;Briskin and Gawienowski 2001) also showed that a reduction in N availability increased hypericin content without resulting in nitrogen deficiency symptoms.…”
Section: Discussionmentioning
confidence: 89%
“…In particular, it has been shown that AM fungi usually increase flower amount, the number of flowering plants in a stand, or flowering earliness (Schenck and Smith 1982;Gaur et al 2000;Scagel 2004;Perner et al 2007;Bunn et al 2009;Asrar et al 2012;Bona et al 2015). However, it also has been found that AM fungi can have no effects on flowering (Linderman and Davis 2004), delay its onset, or increase its duration (Schenck and Smith 1982;Dubský and Vosátka 2000;Saia et al 2014a;Jin et al 2015). Such effects could depend on both the competition for N and photosynthates between AM fungi and flowers (Johnson et al 1982) and the ability of AM fungi to reduce nutrient deficiency or other stresses for the host plant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The leaf area index is related to the plant biomass, while the biomass production requires a lot of water for the photosynthesis processes. The dependency of plant biomass production on the availability of soil water has been reported elsewhere (Saia et al, 2014). In terms of water use efficiency, the production of plant biomass is expected to uptake more water from the soil, therefore water loss through the plant transpiration should be much greater than that by the evaporation from the soil surface.…”
Section: Application Of a Dielectric Measurement Technique For Calculmentioning
confidence: 89%
“…Gao et al, (2007) studied the effect of AMF inoculation on growth performance and Zn uptake by rice genotypes varying in Zn uptake when non mycorrhizal and showed that AMF inoculated plants produced more biomass and took up more Zn than non-mycorrhizal controls. Saia et al, (2014) reported higher biomass production under water stressed conditions in Berseem, clover on AM symbiosis. Increased biomass may be attributed to the enhancement of nutrient uptake offered by AM fungi during active growth stage under aerobic conditions, which satisfied both rice and fungal nutritional needs for growth.…”
Section: Correlation Analysesmentioning
confidence: 90%